Case studies on cost-effectiveness of BRAC provided services in selected enterprises - Halder, Shantana R.; Husain, AM Muazzam (BRAC, 2019)
This case study was conducted on three types of enterprises that have been promoted by BRAC to examine the viability of the enterprises and the relative cost effectiveness of the services delivered by BRAC. Primary data were collected from 106 carp farmers and 102 broiler rearers while secondary data on 97 tailors were used for the study. The net change in annual income per enterprise due to provision of business development services (BDS) by BRAC was found to be Tic 3,371 and Tk. 5,071 respectively for enterprises with and without pre-BRAC experiences. The average amount for all enterprises was Tk. 7,584 or Tk. 4,569 per member-farmer involved in carp polyculture. The BDS provided by BRAC include skill development training, pond preparation and its maintenance and other technical assistance. The cost of BRAC was Tk. 336 per farmer against Tk. 201 realized for the same as service charge. In case of broiler rearing the average net gain in income per lot covering a period of eight weeks due to BRAC programme intervention was Tk. 2,667. This amount was Tk. 3,237 for newly started member-rearers and Tk. 709 for existing ones. The cost of BDS per member rearer was estimated as Tk. 427 while BRAC received Tk. 452 as service charge. In case of tailoring, since 91% of the sample population were previously housewives without involvement in any income generating activity, the current net income from tailoring has been assumed to have accrued due to BRAC intervention. The average net annual income has been estimated as Tk. 7,836 while the average annual cost of BDS per member was Tk. 490 of which 25% was realized by BRAC from each member as service charge. In all three cases, the results show that the enterprises are cost effective some suggestions are made to further improve the cost-effectiveness of the enterprises.